2014
DOI: 10.1039/c3ra45749d
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of ERα/ERβ selective coumarin and chromene derivatives as potential anti-breast cancer and anti-osteoporotic agents

Abstract: Several new coumarin and chromene prototype derivatives have been synthesised and evaluated for their ERa and ERb selective activity. Coumarin prototype compounds 18 & 19 were found to be ERa selective and the most active, exhibiting potential antiproliferative activity against both ER +ve & ER Àve breast cancer cell lines. The surprise finding of the series, however, are the novel prototype III chromenes 45 & 46, with aroyl substitution at the 6 th position. Both the compounds have shown potent antiproliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…81 Hussain et al further conducted a novel synthesis of coumarin derivatives as potent anti-breast cancer agents against ER +ve and ER Àve cell lines. 82 Compound 85 was found to be ER-a selective and most dynamic from all synthesised molecules, exhibiting prospective antiproliferative activity. The docking simulation showed that compound 85 could favorably t well in the receptor cavity of ER-a, following the binding pattern similar to the standard drug.…”
Section: Benzopyrans and Fused Pyranbased Anticancer Scaffoldsmentioning
confidence: 98%
See 1 more Smart Citation
“…81 Hussain et al further conducted a novel synthesis of coumarin derivatives as potent anti-breast cancer agents against ER +ve and ER Àve cell lines. 82 Compound 85 was found to be ER-a selective and most dynamic from all synthesised molecules, exhibiting prospective antiproliferative activity. The docking simulation showed that compound 85 could favorably t well in the receptor cavity of ER-a, following the binding pattern similar to the standard drug.…”
Section: Benzopyrans and Fused Pyranbased Anticancer Scaffoldsmentioning
confidence: 98%
“…At the third position, the 4-methoxyphenyl group forms a hydrophobic interaction with the amino residues Met421, Gly472, His575, Leu298, Phe356, Met340, and Ile373, which are essential features for ER-b binding. 82 Coumarin is a modication of the benzopyran-2-one by directed introduction of a heterocyclic substituent. In most cases, a heteroaryl substituent is introduced at position 3 or 4 of the coumarin ring.…”
Section: Benzopyrans and Fused Pyranbased Anticancer Scaffoldsmentioning
confidence: 99%
“…The antiproliferative activity of coumarin derivatives is well documented. It was in fact reported that coumarins could act as kinase inhibitors [ 150 ], sulfatase inhibitors [ 151 , 152 , 153 ], selective estrogen receptor modulators [ 154 , 155 , 156 ], particularly downregulators [ 157 , 158 , 159 ], 17βHSD3 inhibitors [ 160 ] cellular cycle blockers [ 161 , 162 , 163 , 164 , 165 ], and aromatase inhibitors [ 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 ]. The latter will be examined in more details herein.…”
Section: Coumarins As Enzyme Inhibitorsmentioning
confidence: 99%
“…Since ten years ago, the chromene derivatives have been extensively used as active compounds to treat cancer [26,27] inflammation [28], cardiovascular diseases (CVD) [29]. Moreover, they have been used as antimicrobial [30][31][32], antioxidant [33] antiviral [34], anthelminthic [35], anti-HIV [36], TNF-α-inhibitor [37], estrogenic [38,39] antitubercular [40][41] herbicidal [42], anticonvulsant, antiparkinsonian [43,44], antidepressant [45] and analgesic [46,47] activity. Moreover, some of chromene scaffold are well known as antimicrobial drugs and their analogues such as novobiocin, chlorobiocin and coumermycin Al [48][49][50].…”
Section: Introductionmentioning
confidence: 99%